The optimal choice of pre-launch reviewer. - Gill, D; Sgroi, D (Elsevier, 2012)
We develop a framework in which: (i) a firm can have a new product tested publicly before launch; and (ii) tests vary in toughness, holding expertise fixed. Price flexibility boosts the positive impact on consumer beliefs of passing a tough test and mitigates the negative impact of failing a soft test. As a result, profits are convex in toughness: the firm selects either the toughest or softest test available. The toughest test is optimal when consumers start with an unfavorable prior and receive sufficiently uninformative private signals (an "innovative" product); the softest test is optimal when signals are sufficiently informative.